Analisis Pengaruh Sektor Industri Halal Terhadap Pertumbuhan Ekonomi di Negara-Negara Anggota OKI - Roni Ardiansah; Dwi Surya Atmaja; Luqman Luqman (Institut Agama Islam Yasni Bungo Jambi, Indonesia, 2024)
The aim of this research is to analyze the influence of the halal industrial sector on long-term and short-term economic growth in OIC countries. This research uses a quantitative approach, and the data analysis method uses the Vector Error Correction Model (VECM). Secondary data sources, namely SGIE Report indicator score panel data for 2014-2023 were obtained from DinarStandard and World Bank. The population of this study is the OIC countries in Asia, while the sample is 9 OIC countries in Asia. Data processing uses E Views-10. The results of this research show that in the long term Halal Fashion and Islamic Entertainment Media have a significant positive effect on economic growth, with t-statistic values of 8.308 and 6.372. Halal Food, Halal Cosmetics and Medicines have a significant negative effect on economic growth, with t-statistic values of -4.012 and -3.829. Islamic Finance and Halal Tourism do not have a significant effect on economic growth, with t-statistic values of 0.893 and -0.910. Then, in the short term, Islamic finance has a significant positive effect on economic growth, with a t-statistic of 3.058. Meanwhile, Halal Food, Halal Tourism, Halal Fashion, Islamic Entertainment Media, Halal Cosmetics and Medicines do not have a significant effect on economic growth, with t-statistic values of 0.506, 1.865, 0.256, -1.319 and -1.111.